THE RELATIONSHIP BETWEEN GIVING INCENTIVES AND WORKPLACE STRESS ON JOB SATISFACTION OF GO-RIDE DRIVER PARTNERS IN CAWANG JAKARTA TIMUR - Sari, Putu Indah Mariska; Anggraini, Nenny (Universitas Kristen Indonesia, 2019)
The purpose of this study is to determain the relationship between incentives and workplace stress on job satisfaction of GO-RIDE drivers partners in Cawang, East Jakarta. Everyone has extraordinary potential and has not been fully utilized. Labor is one of the important factors that must be considered by the company, both in term of providing incentives, workplace stress, and job statisfaction. The incentive is one of the strategies implemented by the company to stimulate the workforce to work optimally. And to improve the progress of the company must also pay attention to workplace stress experienced by employess so the employess can work well. Therefore giving incentives and attention to work stress is needed to be able to produce job satisfaction to driver-partners. The type of data in this study is quantitative data, the number of samples is 100 GO-RIDE driver-partners. Data obtained by distributing questionnaires to GO-RIDE driver-partners and calculated with the Likert Scale. This study using SPSS 24 to process the data. The results of this study indicate that there is a relationship between providing incentives with job satisfaction shown in the Spearman Rank correlation coefficient of 0,676. And there is a relationship between workplace stress and job satisfaction shown by the Spearman Rank correlation coefficient of -0,627. Keywords : incentives,workplace stress, job satisfaction